Talin couples the actomyosin cortex to the plasma membrane during rear retraction and cytokinesis - Tsujioka, Masatsune (National Academy of Sciences, 2012)
Contraction of the cortical actin cytoskeleton underlies both rear retraction in directed cell migration and cytokinesis. Here, we show that talin, a central component of focal adhesions, has a major role in these processes. We found that Dictyostelium talin A colocalized with myosin II in the rear of migrating cells and the cleavage furrow. During directed cell migration, talin A-null cells displayed a long thin tail devoid of actin filaments, whereas additional depletion of SibA, a transmembrane adhesion molecule that binds to talin A, reverted this phenotype, suggesting a requirement of the link between actomyosin and SibA by talin A for rear retraction. Disruptions of talin A also resulted in detachment of the actomyosin contractile ring from the cell membrane and concomitant regression of the cleavage furrow under certain conditions. The C-terminal actin-binding domain (ABD) of talin A exhibited a localization pattern identical to that of full-length talin A. The N-terminal FERM domain was found to bind phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P2] and phosphatidylinositol 3,4,5-trisphosphate [PtdIns(3,4,5)P3] in vitro. In vivo, however, PtdIns(4,5)P2, which is known to activate talin, is believed to be enriched in the rear of migrating cells and the cleavage furrow in Dictyostelium. From these results, we propose that talin A activated by PtdIns(4,5)P2 in the cell posterior or cleavage furrow links actomyosin cytoskeleton to adhesion molecules or other membrane proteins, and that the force is transmitted through these links to retract the tail during cell migration or to cause efficient ingression of the equator during cytokinesis.